Efek Konsentrasi Partikel Plastik Terhadap Pertumbuhan dan Kelangsungan Hidup Ikan Bawal Bintang (Trachinotus Blochii) - Razai, Tengku Said; Febrianto, Try; Putra, Imam Pangestiansyah (Dinamika Lingkungan Indonesia, 2020)
Plastic pollution / waste has an impact that will disturb the stability of the ecosystem, especially aquatic organisms such as fish. The main source of plastic contamination comes from household waste that is not managed properly, especially in coastal areas that make the sea as a place of final discharge. Plastic pollution is currently the main problem that is accepted by the environment, especially water. Plastic will dissolve in the waters and will form small sizes (micro-plastic) impacting biota, including fish. Fish including aquatic organisms that can not distinguish between food and plastic particles clearly, thus providing an effect on digestion and growth. The results showed the growth rate of silver Pompanoo with the highest plastic concentration will cause slower growth, the control treatment is the best growth yield compared to treatments that have a plastic content mixed with feed. Growth of weights with the highest concentration of plastic particles is 0,48 gr/week, length growth is 0.75 cm / week, and survival is 69.17% and shows the growth and survival rates are worse or there is a tendency to worsen with an increase in the concentration of plastic contamination . Plastic particles consumed by fish are not digested properly and can even cause the growth response of fish to be slow even to death.